“There should be a room for self-initiated activity” A narrative inquiry on my teaching practices - Hanung Triyoko (IAIN Salatiga, 2011)
This paper is my endeavour to shorten the gap between the realities in my own teaching practices and those practices presented in books and research reports as effective English teaching. In this paper, through narrative inquiry method of writing, I will refer to my experiences to show my way of knowing as well as my way of writing the specific contexts of my teaching of English. Here and then, I may show my subjectivity upon certain issues in the English teaching-learning process but I do this to enable myself go deeper to my personal values. Nonetheless, for the betterment of my classroom practices specifically and the teaching of English for Islamic studies in Indonesia, in general, my inquiry on my own professional practices and the insights on how I should see and make some changes in my teaching as specified by the AAA perspective discussed in details will become a very good start.keywords; Self-Initiated Activity; Narrative Inquiry; AAA Perspective